STRATEGI PEMASARAN DAN PROSEDUR EKSPOR PRODUK NOBASHI EBI PADA TAHUN 2023-2024 DI PT. DUA PUTRA UTAMA MAKMUR, PATI, JAWA TENGAH - Pangestika, Widya; Siahaan, Juan Tiardo; Maulid, Deden Yusman (Universitas Teuku Umar, 2025)
Indonesia’s abundant shrimp production has driven the country to increase foreign exchange earnings through the export of value-added shrimp products. To ensure successful exports, fishery product export procedures must be conducted systematically and in compliance with prevailing regulations. This study aimed to examine the export procedures for nobashi ebi (stretched shrimp) products and to formulate alternative marketing strategies to boost export volume. The research was conducted at PT Dua Putra Utama Makmur using SWOT analysis as the primary analytical tool. Results showed that the export procedure for nobashi ebi consists of 17 sequential process flows carried out in accordance with national and international regulations. Required export documents include HC, Packing List, Invoice, Sales Contract, Test Result Sheet, PEB, NPE, Bill of Lading, COO, and evidence of Telegraphic Transfer. Key institutions involved are BPPMHKP, Customs, EMKL, and shipping companies. Based on the SWOT matrix, recommended marketing strategies to increase export volume include expanding production capacity and export volume by improving the efficiency of raw material supply, enhancing marketing approaches and strengthening bilateral trade relations to penetrate new markets, and conducting comprehensive market research to better understand current market conditions and demand trends